Branding, Packaging, and Digital Marketing Strategies For Processed Fish Business in Pedamaran Village - Dewi Fadila; Marieska Lupikawaty; Abdee Feryawan Saputra; Agra Artha Nastiti; Rina Dwi Aprianti (Manunggal Halim Jaya, 2022)
Pedamaran 6 Village is one of the villages at Pedamaran District in Ogan Komering Ilir (OKI)South Sumatera Province which has wide lakes and rivers and produces abundant fish resources. The fishes that live in fresh water such as Tawes Fish (Barbonymus Gonionotus), Sepat Fish (Trichopodus tricopterus), and others are very much found in the area. The community in Pedamaran 6 village utilizes these natural resources as the majority of the business fields there. This includes Mrs. Dede Oktarina, who sells “Kemplang” as the majority of her business. Despite having potential resources, sales of Mrs. Dede's processed fish products tend to stagnate. she has not been able to market their cultivated fish and processed fish to urban areas. Their inability to disseminate this business is based on the distance between Pedamaran village and the city which is quite far ± 100 km and takes about 2 hours 49 minutes to get to the destination. In addition, they lack of awareness of the importance of Branding, Packaging, and Digital Marketing which is indispensable in the sales process in order to thrive in the digital era as it is now. The packaging that Mrs. Dede uses still uses plastic and makeshift materials. This causes the processed products to not last long and do not attract market share. The solution we offer is to introduce a sales strategy through Branding, Packaging and Digital Marketing which is expected to be able to increase the quality of sales and profits from Ms. Dede's processed fish products. The output of this program is the creation of a good logo of product and to create a website.